Analisis Produktivitas Tanaman Padi di Kabupaten Badung Provinsi Bali - K. Agus Wirawan; IK. Budi Susrusa; IGAA. Ambarawati (JURNAL MANAJEMEN AGRIBISNIS, 2014)
The development of agricultural production in Badung Regency is more emphasized on increasing its productivity compared to the enhancement of the land area. Local governments in calculating rice production using the method known as 'tile'. Results tile is very important because it is used as the official statistical data to calculate production, productivity, forecasting, etc.. Handling of production factors in the process of planting, fertilizer use, chemical product, pest management, and lack of knowledge about the tile farmers make rice productivity did not increase significantly. This research aims to assess development of rice plants productivity, to identify and determine factors affecting rice plants productivity in Badung, reviewing, analyzing the magnitude of gap between the estimated production produced by tile to rill production of selected farmers on rice fields.The method used is multiple linear regression and the average test pairs with 550 plots using secondary data and primary data sample tile by 41 respondents. Research results show that variables which have positive relation to the yied tile variable is the amount of clumps of rice, seed, and  fertilizer. Whereas, the variable that have negative relation is the presence or absence of pesticides, plant pests attacks. The coefficient of determination the five independent variables in the tile result of rice is by 82.1%, and 17.9% explained by other variables. With the confidence level of 95% the five independent variables in the regression equation simultaneously can be used on explaining the outcome variable of       rice tile. All the independent variables include (1) The number of clumps, (2) quantities of seed; (3) amount of fertilizer; (4) amount of pesticides, and (5) whether there is any plant pests attacks have a significant influence on yieldof rice tile. Based on primary data obtained from 41 samples of rice farmers, there is a difference between the estimated production produced by the rice tile to the real farmers results. The average the estimated value of the rice tile results is by 81.66 kg/acres while the real production output is by 69.10 kg/acres. The results of the estimation rice production is higher 18.18% compared to the real production.This estimate gives a higher estimate of the impact on local rice production and farmers' income estimates excess of Rp 48,500 per are.